1995
DOI: 10.1007/bf01438868
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the specific heat capacity of liquid Au-Sn alloy based on the ideal-associated solution model

Abstract: Tile specific heat capacity of Au Sn liquid alloy was analyzed using tile ideal associated solution model assuming associated compotmds Au~Sn, AuSn, and AuSn,. Based on this model, all of the specific heat capacity, heat of mixing. and activity are described over a wide temperature range. Further, it became clear that the st.ruination of mole numbers of tile species in the liquid alloy shows a minium at the stoichiometric composition of Au3Sn. which implies that the liquid is tile most ordered at this composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This tendency is continued in the present work. By using an ideal-associate model, Wasai et al 21 recently fitted experimental data of heat capacity and deduced expressions of specific capacity for liquid Au-Sn with the compositions of Au 3 Sn, AuSn, and AuSn 2 , which indicates that the mixing enthalpy of liquid may become less negative with increasing temperature. Such temperature dependence is in good agreement with the present work.…”
Section: Au-sn Binary Systemmentioning
confidence: 98%
“…This tendency is continued in the present work. By using an ideal-associate model, Wasai et al 21 recently fitted experimental data of heat capacity and deduced expressions of specific capacity for liquid Au-Sn with the compositions of Au 3 Sn, AuSn, and AuSn 2 , which indicates that the mixing enthalpy of liquid may become less negative with increasing temperature. Such temperature dependence is in good agreement with the present work.…”
Section: Au-sn Binary Systemmentioning
confidence: 98%
“…Hence, tracking the structural evo lution in melts changing with temperatures can not only deepen the understanding of glass formation, but also uncover novel phenomena in the liquid state. For example, metallic liquids of noble metals with polyvalent elements often show non-linear magnetic, electric and/or thermodynamic properties [1][2][3][4][5][6][7][8][9][10][11]. Vinckel et al [11] found non-linear changes in electrical resistivity and absolute thermoelectric power in liquid silver-gallium (Ag-Ga) alloys with different compositions, which is a prototype model system for studying noble-polyvalent metallic alloys, such as Ag-Ge, Ag-In, Cu-Ga, Au-Ga. Shirakawa et al [12] proposed the correlation of electronic density of states with the concentration-concentration fluctuation in the long-wavelength limit in liquid Ag-polyvalent alloys, and further pointed out that liquid noble-polyvalent metals could have short range ordered states when the atomic size ratio for the constituents is less than 1.4.…”
Section: Introductionmentioning
confidence: 99%